De novo 15q13.3 microdeletion with cryptogenic west syndrome. Issue 10 (8th August 2013) - Lacaze, Elodie; Gruchy, Nicolas; Penniello‐Valette, Marie‐José; Plessis, Ghislaine; Richard, Nicolas; Decamp, Mathieu; Mittre, Hervé; Leporrier, Nathalie; Andrieux, Joris; Kottler, Marie‐Laure; Gerard, Marion
ABSTRACT West syndrome is a well‐recognized form of epilepsy, defined by a triad of infantile spasms, hypsarrhythmia and developmental arrest. West syndrome is heterogenous, caused by mutations of genes ARX, STXBP1, KCNT1 among others; 16p13.11 and 17q21.31 microdeletions are less frequent, usually associated with intellectual disability and facial dysmorphism. So‐called "idiopathic" West syndrome is of better prognostic, without prior intellectual deficiency and usually responsive to anti‐epileptic treatment. We report on a boy falling within the scope of idiopathic West syndrome, with no dysmorphic features and normal development before the beginning of West syndrome, with a good resolution after treatment, bearing a de novo 15q13.3 microdeletion. Six genes are located in the deleted region, including CHRNA7, which encodes a subunit of a nicotinic acetylcholine receptor, and is frequently associated with epilepsy. Exploration of the 15q13.3 region should be proposed in idiopathic West syndrome. © 2013 Wiley Periodicals, Inc.